Progress in Allergy Signal Research on Mast Cells: The Role of Histamine in Immunological and Cardiovascular Disease and the Transporting System of Histamine in the Cell - Hiroshi Ohtsu (Elsevier, 2008)
Since its discovery in 1910, histamine has been regarded as one of the most important biogenic amines in the medical and biological fields. This article summarizes the information about the role of histamine in allergic situations, atherosclerosis, and autoimmune encephalomyelitis, especially focusing on our study with histidine decarboxylase gene knockout mouse. In the allergic bronchial asthma model, histamine positively controls eosinophilia but not bronchial hypersensitivity. Histamine is proved to be an important substance that controls body temperature and respiration in systemic anaphylaxis but its role in controlling blood pressure is minor. Histamine also plays a role in inducing atherosclerosis in the mouse model. We showed that experimental autoimmune encephalomyelitis (EAE) is significantly more severe in histamine-deficient mice with diffuse inflammatory infiltrates in the brain and cerebellum, including a prevalent granulocytic component. Histamine is mainly produced in mast cells and basophils in hematopoietic cells. We've shown that mast cells not only produce histamine, but also uptake it from the environmental medium and release it by allergic stimulants. The protein used for the plasma transport of histamine in basophils was identified as organic cation transporter (OCT3). Keywords:: histamine, histidine decarboxylase, knockout, immunology, cardiovascular disease, allergy